Outcome of revascularization in moyamoya disease: Evaluation of a new angiographic scoring system - Sahoo, Siddhartha; Suri, Ashish; Bansal, Sumit; Devarajan, S; Sharma, Bhawani (Asian Journal of Neurosurgery, 2015)
Background: Moyamoya disease (MMD) is a chronic progressive cerebrovascular occlusive disease affecting commonly the anterior circle of Willis. Matushima grade inadequately reflects the angiographic changes postrevascularization procedure. Aims: To analyze the clinical and angiographic outcome of revascularization procedures (direct [ST-middle cerebral artery (MCA) anastomosis] and indirect [encephalo-duro-arterio-myo-synangiosis (EDAMS)]) in MMD and validate a new angiographic scoring system. Materials and Methods: Retrospective study included symptomatic patients of MMD who underwent revascularization; both indirect and combined methods between January 2002 and April 2012. Follow-up angiography was done after at least 3 months. We devised a novel scoring system the "angiographic outcome score" (AOS) including reformation of distal MCA and anterior cerebral artery, regression of basal moyamoya vessels, leptomeningeal collaterals and overall perfusion. AOS was applied to the angiograms independently by a neuroradiologist and a neurosurgeon that were blinded toward its preoperative or postoperative status. Results: Totally 33 patients underwent 36 EDAMS and 4 combined procedures (EDAMS + ST-MCA bypass). The mean follow-up was 20 months. None had recurrent transient ischemic attack or fresh infarct. Postoperative AOS was significantly higher than preoperative AOS. The Spearman rho showed positive correlation between Matushima grade and postoperative AOS. Significant regression of basal moyamoya vessels and increase in number of loci of transdural collaterals was seen. Conclusions: EDAMS is a simple yet effective method of revascularization in both pediatric as well as adult age groups. AOS is a simple, precise and easily reproducible scoring system, which reflects the favorable angiographic changes after revascularization.
Keywords: Angiography; encephalo-duro-arterio-myo-synangiosis; moyamoya disease; revascularization